Calcific Tendinitis in the Elbow Presented as Acute Tennis Elbow - Bhandari, Ravi; Sinha, Ritesh; Kayastha, Nirab; Joshi, Amit (Journal of Nepal Health Research Council, 2020)
Calcific tendinitis occurs frequently in shoulder and hip region. Its occurrence in elbow joint is frequently misdiagnosed because of its rare incidence and similar clinical presentation with other acute conditions of elbow like trauma, infection and tennis elbow. Characteristic symptoms of this condition are acute onset of pain, tenderness and swelling on the lateral aspect the elbow. Plain Radiograph is the primary modality to distinguish and evaluate this condition. Awareness and familiarity with this condition helps in early diagnosis and avoids unnecessary treatments and biopsy as this condition is self-limited.Keywords: Calcific tendinitis; self-limited; tennis elbow.